Frameworks for international press coverage of external interference in the formation of the Iraqi government Analytical study for the Saudi Al-Sharq Al-Awsat and Kayhan Al-Arabi-Iranian newspapers for the period (1/1/2018 - 31/12/2018) - Al-Rubaie, Bidaa Hussein Nasser; Dabkh, Widad Ghazi (ALBAHITH ALALAMI, 2020)
This research deals with the frameworks and mechanisms of international press coverage of the issue of foreign interference in the formation of the Iraqi government in the Saudi newspapers Asharq Al-Awsat and Kayhan Al-Arabi Iran and how this topic was addressed in the two newspapers. The frameworks for international press coverage of external interference in the formation of the Iraqi government. ”This research is one of the descriptive research that adopted the survey method، which made it possible to use the content analysis tool to analyzethe content of the two newspapers، whose numbers are (624) from thenewspapers (Al-Sharq Al-Awsat Al-Saudi Arabia and Kayhan Al-Arabi Iran) from (1/1/2018 to 31/12/2018)، and the research has reached themost important results، the framework of the conflict ranked first amongthe frameworks used by the research papers، and the framework of theproposed solutions ranked second in the two newspapers.